Organizational Strategies and Performance in the Banking Industry Focused on the Transnational Banks in Sierra Leone: An Ex Post Facto Study - Hassan Elsan Mansaray (Budapest International Research and Critics University, 2020)
To successfully examine the banking strategies used by transnational Banks in Sierra Leone to improve their performances, the researcher used a longitudinal research method to carry out the study. The method is used so as to achieve the research goals by focusing on the ensuing operating challenges to survive, grow and meets their set goals with the purpose of maintaining their core mandate as financial intermediaries as well as agents of economic growth in Sierra Leone and beyond. The study noted that the transnational Banks in Sierra Leone’s organizational strategies support every individual to comprehend where the banking business is moving and how the banks willpower can influence those strategies. Equally, the study further observed that their organizational strategies also explain their market positions and clarify how the transnational banks communicate with customers, competitors, and departmental changing structures to convey success. Based on the entire study, the transnational banks are on the advanced trajectory which can make them continuously achieve competitive advantage in the banking industry in Sierra Leone, since their strategies are positive towards meeting their goals. Although some improvements are needed on their marketing strategies, knowledge about bank products and services, innovation, strategy orientation, as well as wide improvement on employees’ satisfaction strategy to increase commitment and loyalty.